Barefoot in the park. - Clark, Phillip, 1941-; Coe, Richard L. (Richard Livingstone), 1914-1995; Loy, Myrna, 1905-1993; Nichols, Mike; Penberthy, Beverly; Simon, Neil; Szabo, Sandor, 1915-1997 (1966)
National Theatre, Saint Subber presents Myrna Loy, Sandor Szabo, Beverly Penberthy, Phillip Clark, in Neil Simon's new comedy "Barefoot in the Park," setting designed by Oliver Smith, lighting by Jean Rosenthal, costumes by Donald Brooks, directed by Mike Nichols.